The Dynamics of the Alfvénic Oval. (August 2021) - Keiling, Andreas
Abstract: The auroral oval is a well-established concept, introduced more than five decades ago. The Alfvénic oval, on the other hand, is a very recent concept, which has been revealed in both observational and numerical studies. This is the first review of the global Alfvénic oval, while also defining primary, secondary and tertiary layers of the Alfvénic oval. The focus lies on the large-scale dynamic properties of the global Alfvénic oval in relation to the AE index, substorm phases, storm phases and solar wind/IMF conditions. Statistical data recorded above and below the nominal auroral acceleration region are reviewed, together with results from global simulation studies. The Alfvénic oval's relation to the auroral oval is also reviewed. This review demonstrates that the Alfvénic oval is well enough defined and investigated to give it its name, and it demonstrates that our understanding allows for the prediction of the Alfvénic oval under various conditions. Highlights: First review of the dynamic Alfvénic oval. Defining three layers: primary, secondary, and tertiary Alfvénic ovals. Dynamic properties in relation to the AE index, substorms, storms and solar wind/IMF parameters are reviewed. Alfvénic oval's impact on the auroral oval is reviewed.